2014
DOI: 10.4103/0975-962x.144735
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive odontogenic myxoma of the maxilla

Abstract: Odontogenic myxoma (OM) is a relatively rare benign odontogenic tumor of mesenchymal origin. OM is more common in the mandible than in the maxilla. It is an asymptomatic lesion that shows an infiltrative growth pattern. When the maxillary sinus is involved, it often fills the entire antrum. Odontogenic tumors are uncommon in the maxillary molar area, which often leads to diagnostic dilemma as this region of the maxilla is in the vicinity of vital structures, and radiographic overlapping of structures is always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[ 13 ] Sivakumar and Kavitha suggested that odontogenic myxoma is a tumor of a dual fibroblastic-histiocytic origin and the cells comprising odontogenic myxoma are of myofibroblastic origin. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Sivakumar and Kavitha suggested that odontogenic myxoma is a tumor of a dual fibroblastic-histiocytic origin and the cells comprising odontogenic myxoma are of myofibroblastic origin. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the present case to confirm mucoid reaction alcian blue staining was done which showed positive staining, this finding is in accordance with the results of Kiresur and Hemavathy. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Myxomatous matrix showed a negative reaction for all the antibodies used. [ 9 10 11 ] Bcl2 indicates the proliferative activity of tumor cells. Since myxomas are aggressive neoplasms, in the present case, this marker was used to assess the tumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…After a large resection, this patient did not experience disease recurrence over a 4-year follow-up period [ 10 ]. Kiresur and Hemavathy also performed an extended resection of the jaw in a 17-year-old patient because resection procedures minimize the risk of involvement of vital structures and reduce the recurrence rate [ 11 ]. Limdiwala and Shah described two odontogenic myxomas of the maxillae, both in adults that underwent conservative surgery, but follow-up was not described in this paper [ 12 ].…”
Section: Discussionmentioning
confidence: 99%